Molecular and functional characterization of a secreted lipase from Botrytis cinerea - Reis, H; Pfiffi, S; Hahn, M (Molecular plant pathology, 2005)
SUMMARY A previous study has indicated that a cutinolytic lipase from Botrytis cinerea was required for penetration of an intact plant host cuticle and infection (Comménil et al., 1998, Physiol. Mol. Plant Pathol. 52, 1–14). In order to clarify the role of this lipase, the corresponding gene (lip1) was cloned. In vitro, the lip1‐encoded lipase was inducibly expressed and subject to catabolite repression. On the leaf surface, the cuticle served as an inducer. lip1 knock‐out mutants lacked lipase activity; however, no reduction of virulence was observed. To further eliminate cutinolytic activity, the gene encoding cutinase A was also disrupted. In lip1cutA double mutants, extracellular esterases were largely eliminated in vitro and greatly reduced on the leaf surface; yet these mutants also retained full pathogenicity in various host systems. Our data indicate that cutinase and esterase activities are secreted by germinating B. cinerea spores on the surface of host leaves, but they do not seem to be required for host cuticle penetration.